Simulasi Mikromagnetik untuk Menganalisis Dampak Bentuk Geometri terhadap Sifat Magnetik Material Permalloy - vavionita, Fenni; Indriawati, Anisa; Aldila, Herman (Jurusan Fisika, Universitas Bangka Belitung, 2025)
The development of ferromagnetic material technology is currently experiencing very rapid progress in various fields. One of the technological developments in the field of developing ferromagnetic materials based on thin layers of soft magnetic properties is used in the manufacture of recording heads, Magnetic Tunnel Junction (MTJ) contained in Magnetoresistive Random Access Memory (MRAM) and various sensors. One example of a ferromagnetic material with softmagnetic properties is permalloy. Permalloy has high permeability and a magnetic moment configuration that is easily controlled with small changes in the magnetic field. The advantage of permalloy is that apart from its high permeability, it also has low coercivity, resistance to oxidation, and significant anisotropic magnetoresistance. Therefore, in this research micromagnetic simulations have been carried out for thin layers using permalloy material. This research was carried out using the OOMMF (Object Oriented Micromagnetic Framework) software simulation to obtain the influence of the shape of the permalloy material on the magnitude of the magnetization value, coercivity value and anisotropy energy value produced due to the influence of an external magnetic field. The research results show that the shift in the magnetic wall domain in this study produces different magnetization values ​​in each form of permalloy material, the difference in shape also affects the field coercivity value and the anisotropy energy value. This can be seen when the external magnetic field applied is 5000 Oe, the magnetization value in form 1 is 0.99997, with a coercivity field of 680 Oe and an anisotropy energy value of 5.72 × 10-28, for form 2 it has a magnetization value of 0, 9806628, with a coercivity field of 1240 Oe and an anisotropy energy value of 3.55 × 10-25, and form 3 has a magnetization value of 0.942093 with a coercivity field of 960 Oe and an anisotropy energy value of 1.00 × 10-25. An increasing magnetization value indicates that the material is saturated, and the resulting anisotropy energy value becomes smaller.